The assessment of 2D animation e-module suitability usage in Malaysia community college - Ismail, Mohd Erfy; Hashim, Suhaizal; Masek, Alias (Primrose Hall Publishing Group, 2019)
Apart from the extensive facilities, the expertise and competence of lecturers is seen as one of the important things to complement the implementation of the policy especially in the teaching and learning process. However, teaching in the form of explanation may force them to not be bored and not interested in learning topics conducted by lecturers. Therefore, this study aimed to evaluate the suitability of the Basic 2D Animation E-Module in terms of content, interface design and user acceptance levels. This e-module software through the Microsoft PowerPoint application based on the Basic 2D Animation curriculum subject, Malaysia Community College Certificate Program. This quantitative study was conducted using a survey method using a questionnaire instrument distributed to 50 students from 3rd semester of 2D Animation Programs. The three Community Colleges involved in this study were in Segamat, Kuala Langat and Kepala Batas. The data obtained was analyzed based on frequency, mean and standard deviation. The study found that the content level of suitability content was high with a mean score of 3.63. Evaluation on the suitability level of the interface design is also at a high level with a mean score of 3.63, while acceptance level of the user shows the mean score of 3.62 which also on a high level. All respondents agree that the application of the Basic 2D Animation E-Module used is suitable and meets the requirements for the implementation of teaching and learning. This e-module can be expanded to enable its implementation to be more attractive and effective.